The role of metalloproteinases and their tissue inhibitors in adipose tissue remodelling and whole-body lipid distribution: a cross-sectional clinical study. (26th February 2015) - Fenech, Matthew; Gavrilovic, Jelena; Malcolm, Paul; Toms, Andoni; Turner, Jeremy
Abstract: Background: Metabolically unhealthy obesity is associated with insulin resistance. Dysfunctional adipose tissue remodelling might explain features of this disorder, such as chronic white adipose tissue inflammation, adipocyte hypertrophy, and ectopic lipid deposition. Metalloproteinases and their tissue inhibitors (TIMPs) have been implicated in human adipose tissue remodelling. In a cross-sectional study, we investigated the association of adipose metalloproteinase and TIMP expression with whole-body lipid distribution and insulin resistance. Methods: Healthy women undergoing elective surgery donated fasting blood samples (for calculation of homoeostasis model assessment of insulin resistance [HOMA2-IR], the primary outcome). At operation 2 cm 3 biopsy samples of subcutaneous and visceral adipose tissue were obtained. 1 cm 3 was fixed, paraffin-embedded, and stained for adipocyte size quantification, and RNA was extracted from the remaining tissue for quantitative RT-PCR analysis. The women also underwent whole-body MRI for analysis of fat distribution. Findings: 26 women were recruited (mean age 50·3 years, SD 13·1) into five body-mass index categories (18·5–24·9 kg/m 2 [n=12, 46·1%], 25–29·9 [n=6, 23·1%], 30–34·9 [n=3, 11·5%], 35–39·9 [n=3, 11·5%], >40 [n=2, 7·8%]). Mean fasting glucose was 5·29 mmol/L (SD 0·66), mean fasting insulin 71·29 pmol/L (47·72), and mean HOMA2-IR 1·35 (0·91). HOMA2-IR correlated with body-mass index ( r =0·73, p<0·0001), subcutaneous and visceral adipose tissue volumes ( r =0·94 and r =0·87, respectively; both p<0·0001), and hepatic fat fraction ( r =0·57, p=0·013). Visceral adipose tissue MMP14 expression correlated strongly with hepatic fat fraction ( r =0·944, p<0·0001), HOMA2-IR ( r =0·74, p=0·01), and visceral adipose tissue volume ( r =0·74, p=0·036). Subcutaneous adipose tissue TIMP3 expression correlated with subcutaneous adipocyte area ( r =0·72, p=0·029), but not with HOMA2-IR ( r =–0·53, p=0·062). Interpretation: The results suggest that metalloproteinases and TIMPs regulate adipose tissue remodelling and distribution. MMP14 has been implicated in collagen turnover in pre-adipocyte differentiation, whereas TIMP3 may modulate the shedding of DLK1, a regulator of adipogenesis. In our concurrent in-vitro study, we have shown that human adipocytes express metalloproteinases and TIMPs, and that their expression varies with inflammatory stimulation. These proteins might therefore integrate inflammatory signals with dysregulated adipose remodelling in metabolically unhealthy obesity. Funding: British Heart Foundation, Diabetes Research & Wellness Foundation Open Funding 2011.